Pendekatan art therapy dalam kalangan kanak-kanak mangsa pencerobohan pengganas Lahad Datu: satu kajian kes - Musa, Mohd Makzan (Bahagian Pengurusan Psikologi, Jabatan Perkhidmatan Awam Malaysia, 2018)
This paper discussed the modality of Art Therapy used in children of terrorist intrusion in Lahad Datu, Sabah. Art Therapy as a modality of creative intervension involving drawing and coloring have been used as a method of data collection. Visual data in the form of illustrated images along with transcriptional oral data has been used to understand the psychosocial issues resulting from terrorist intrusions in children. The findings of this study show that Art Therapy as a creative intervention modality can be used to understand the psychosocial issues experienced by children of terrorist intrusions. The result of this study also found that children involved in geopolitical conflicts experienced psychosocial issues involving fear, destructions, loss, stress, trauma, sadness, anger, adaptation, pain and death. The implication of this study found that the modality of Art Therapy can be applied to victims of terrorist invasions in children.